Arsenic removal from aqueous solutions and groundwater using agricultural biowastes-derived biosorbents and biochar: a column-scale investigation. Issue 6 (12th May 2019) - Tabassum, Riaz Ahmad; Shahid, Muhammad; Niazi, Nabeel Khan; Dumat, Camille; Zhang, Yongqing; Imran, Muhammad; Bakhat, Hafiz Faiq; Hussain, Imtyaz; Khalid, Sana
Abstract: In this study, column-scale laboratory experiments were performed to evaluate the arsenic (As) removal efficiency of different agricultural biowastes-derived biosorbents (orange peel, banana peel, rice husk) and biochar, using As-containing solutions and As-contaminated groundwater. All the biosorbents and biochar efficiently removed (50–100%) As from groundwater (drinking well water). Arsenic removal potential of biosorbents varied with their type, As concentration, contact time, and As solution type. After 1 h, the As removal efficiency of all the biosorbents was 100%, 100% and 90% for 5, 10, and 50 µg/L As-contaminated groundwater samples, respectively; and it was 50%, 90%, and 90% for 10, 50, and 100 µg/L As solutions, respectively. After 2 h, all the biosorbents and biochar removed 100% As from aqueous solutions except for 100 µg/L As solution. This showed that the biosorbents and biochar could be used to reduce As contents below the WHO safe limit of As in drinking water (10 µg/L). Fourier transform infrared (FTIR) spectroscopy indicated possible role of various surface functional moieties on biosorbents/biochar surface to remove As from solution and groundwater. This pilot-scale column study highlights that the biosorbents and biochar can be effectively used in remediation of As-contaminated groundwater, although the soluble salts in groundwater increased after treatment with biochar.